2016
DOI: 10.1097/qai.0000000000000949
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of BST2 Polymorphisms in Mother-to-Child Transmission of HIV-1 and Adult AIDS Progression

Abstract: BST-2/Tetherin is a restriction factor that prevents Human immunodeficiency virus type 1 (HIV-1) release from infected cells and mediates pro-inflammatory cytokine production. This study investigated the risk conferred by single nucleotide polymorphisms (SNPs; rs919266, rs9192677 and rs9576) at BST-2 coding gene (BST2) in HIV-1 mother-to-child transmission and in disease progression. Initially, 101 HIV-1+ pregnant women and 331 neonates exposed to HIV-1 from Zambia were enrolled. Additional BST2 SNPs analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…IFNα, IFNβ, IFNκ, IFNε, IFNω) or "pseudo"-genes (13 different IFNα subtypes), numerous type I IFN signaling pathway components and ISGs [16]. However, several studies have pointed out the importance of SNP related to the type I IFN pathways on the clinical outcome of HIV-1 disease [103][104][105][106][107][108][109][110][111][112][113][114][115][116][117]. Rapid progression of HIV-1 infection, altered viral load and CD4T cell count were associated with TLR9 polymorphisms [103][104][105].…”
Section: Host Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…IFNα, IFNβ, IFNκ, IFNε, IFNω) or "pseudo"-genes (13 different IFNα subtypes), numerous type I IFN signaling pathway components and ISGs [16]. However, several studies have pointed out the importance of SNP related to the type I IFN pathways on the clinical outcome of HIV-1 disease [103][104][105][106][107][108][109][110][111][112][113][114][115][116][117]. Rapid progression of HIV-1 infection, altered viral load and CD4T cell count were associated with TLR9 polymorphisms [103][104][105].…”
Section: Host Factorsmentioning
confidence: 99%
“…Several studies have reported controversial results on the influence of retroviral restriction factor SNPs (e.g. APOBEC3, SAMHD1, and BST2) on HIV-1 disease status [110][111][112][113][114][115][116][117]. Although the clinical relevance of these genetic variants during HIV-1 infection has been emphasized, their biological significance has seldom been examined [45,118].…”
Section: Host Factorsmentioning
confidence: 99%
“…Insertion/deletion (indels) polymorphisms in the promoter region (rs3217318 and rs10415893) of the BST2 gene were associated with lower transcriptional activity and faster disease progression in a Spanish cohort . The BST2 rs9576A allele was nominally associated with protection during breastfeeding ( p = 0.019) and individuals with the rs919266 GA genotype showed slower disease progression to AIDS ( p = 0.033) …”
Section: Introductionmentioning
confidence: 99%
“…34 The BST2 rs9576A allele was nominally associated with protection during breastfeeding (p = 0.019) and individuals with the rs919266 GA genotype showed slower disease progression to AIDS (p = 0.033). 37 To date, the prevalence of the TRIM5α rs11038628 G249D polymorphism has described in HIV-infected individuals from India. 22 So far, the effect of TRIM5α (rs10838525, rs7127617 and rs904375) and BST2 (rs3217318 and rs71694748) polymorphisms in HIVinfected and healthy individuals has not been examined in India.…”
mentioning
confidence: 99%
“…Moreover, polymorphisms of some genes such as BST2,15 BSSL,16 APO-BEC3H17 have been proposed to be related to the progression of HIV infection. We therefore hypothesize that IL-27 gene polymorphism is associated with HIV infection and its progression.…”
mentioning
confidence: 99%